Testing UML design model for web-based system - Omar, Mazni; Katuk, Norliza (2005)
UML has been widely used as a modeling tool in software development. Software developed with UML has to be tested to assure its qua1ity and to prevent faults. Current practice in UML design evaluation consists of walkthrough and inspections. However, these techniques are too complex and tedious because the reviewer needs to track large amount of information. Furthermore, the lack of assessment of design quality, and deficiency in detecting and correcting design fault in the model can increase the total software development costs and time to market. This indicates that the need of testing and validating design model for web-based applications is high. Therefore, this study intends to justify whether the DCD criteria can be used to derive suitable test cases for web-based application UML design model.